Reduced astrocyte density underlying brain volume reduction inactivity-based anorexia rats. (3rd April 2018) - Frintrop, Linda; Liesbrock, Johanna; Paulukat, Lisa; Johann, Sonja; Kas, Martien J.; Tolba, Rene; Heussen, Nicole; Neulen, Joseph; Konrad, Kerstin; Herpertz-Dahlmann, Beate; Beyer, Cordian; Seitz, Jochen
Abstract: Objectives: Severe grey and white matter volume reductions were found in patients with anorexia nervosa (AN) that were linked to neuropsychological deficits while their underlying pathophysiology remains unclear. For the first time, we analysed the cellular basis of brain volume changes in an animal model (activity-based anorexia, ABA). Methods: Female rats had 24 h/day running wheel access and received reduced food intake until a 25% weight reduction was reached and maintained for 2 weeks. Results: In ABA rats, the volumes of the cerebral cortex and corpus callosum were significantly reduced compared to controls by 6% and 9%, respectively. The number of GFAP-positive astrocytes in these regions decreased by 39% and 23%, total astrocyte-covered area by 83% and 63%. In neurons no changes were observed. The findings were complemented by a 60% and 49% reduction in astrocyte (GFAP) mRNA expression. Conclusions: Volumetric brain changes in ABA animals mirror those in human AN patients. These alterations are associated with a reduction of GFAP-positive astrocytes as well as GFAP expression. Reduced astrocyte functioning could help explain neuronal dysfunctions leading to symptoms of rigidity and impaired learning. Astrocyte loss could constitute a new research target for understanding and treating semi-starvation and AN.